Foraminifera as health bioindicators in nearshore and offshore Brazilian coral reef sediments - Oliveira-Silva, Patricia; Barbosa, Cátia Fernandes; Seoane, José Carlos Sícoli; Ferreira, Beatrice Padovani; Cordeiro, Renato C.; Soares-Gomes, Abilio; Almeida, Carine M. de; Queiroz, Gustavo P.; Duran, Débora; Lamana, Thais (Anuário do Instituto de Geociências, 2006)
Abstract